Websites dos arquivos públicos estaduais: uma ferramenta para a divulgação da informação arquivística - SANTOS, Larissa Santana dos (2018)
This work had as a objective to the demonstrate the benefits of using the internet through archives, to disseminate the archival information to a society. Thus, this study aimed to investigate and identify Brazilian state archives are using this tool to spread their collections, services and access to information through the use of websites available online. To achieve the goal of the research done through a quantitative approach, where the instrument used to collect the data was a table checklist, containing four criteria for analysis, which force the author on the basis of the "general guidelines for the construction archives websites "created by CONARQ in the year 2000. The results obtained demonstrate that few state public archives have websites available on the internet and, the few that they have, only a small portion presents in their information on the archive, the collection and its services in a reasonably good interface. Concludes to all public state archives, mainly in the North and Northeast, are urged to advanced and in fact promote a diffusion of archives through the internet through its websites.